A proper dyaloge betwene a gentillman and an husbandman - Parker, Douglas H. (Douglas Harold), 1942- (University of Toronto Press, 1996)
A proper dyaloge is important within the context of reformation literature for a number of reasons and it is an excellent introduction to early Protestant critiques of the Church.